Analisis Penyusunan Laporan Keuangan UMKM Berdasarkan SAK EMKM pada Toko Sahrul di Kabupaten Batubara - Nadia Anzani; Marliyah; Laylan Syafina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
UMKM Toko Sahrul faces several problems in its financial reporting, due to a lack of knowledge in recording financial reports based on ЅАК ЕМКM. The aim of this research is to analyze the preparation of MSME financial reports based on SAK EMKM at the Sahrul Shop, Pematang Kuing Village, Batubara Regency. This research uses a qualitative descriptive method. This research uses primary and secondry data types. Primary data is obtained directly from the company, while secondary data. in the form of relevant documents, scientific articles and books. Data collection was carried out through observation, interviews and documentation. Next, the data is analyzed based on data reduction, data presentation, and verification/drawing conclusions. The results of the research show that MSMEs at the Sahrul Shop in Pematang Kuing Village, Batubara Regency have not implemented SAK EMKM in recording their financial reports, because there are several obstacles such as the absence of supervision from certain parties, lack of understanding from MSME owners regarding the income and profits earned each month or per year and a lack of knowledge in the field of accounting to support the decision-making process regarding future business development.